Influence of different types of bedding material on the prevalence of pododermatitis in rabbits. (April 2020) - Wolf, P.; Speers, R.; Cappai, M.G.
Abstract: Pododermatitis is a disorder with a complex etiology, because potentially determined by various factors such as posture, nutrition and genetics. In the case of presence of pododermal lesions, it is often noticed that rabbits go to eat at the bowl less frequently, but an evident weight loss is not always perceptible. In fact, similarly to poultry, overweight animals seem to be prone to the onset of pododermatitis. An experiment was carried out to test the effect of different types of bedding material (straw vs. wood shavings vs. coarse bark mulch vs. cotton) on the prevalence of pododermatitis in 30 fattening Separator rabbits. Once a week, the four experimental runs were assessed for contamination (macroscopic contamination by faeces/urine/litter) as well as for lesion scoring of the footpad. In addition, the water and ammonia binding behaviour of bedding was tested. The most favourable values as to dry matter, NH3 ( p < .05) and also scoring of the litter were generally observed when cotton was used as bedding material. This is probably due to the high water binding capacity, the faster water release and the structural effects of the material itself (softness). By contrast, the structure of the coarse bark mulch was not suitable for binding liquids (especially urine) and led to increased contamination of the barrels. These results suggest that rabbits with an increased tendency to sore soles should be kept on bedding materials with desirable physical properties (e.g. cotton litter). Highlights: Footpad lesions are an issue for health and welfare of both farmed and pet rabbits. The quality of litter acts as a co-factor on the onset of lesions. Body weight and physical characteristic of the bedding material show an interplay in the development of pododermatitis. High DM content and low NH3 are desired physico-chemical parameters to evaluate the fitness of bedding material. In descending order cotton, wood shavings, coarse bark bulk and straw displayed best to least favourable characteristics.